2014
DOI: 10.1111/jfpp.12216
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Olive Oil Yield and Quality Through Enzyme-Assisted Mechanical Extraction, Antioxidants and Packaging

Abstract: The present article investigates the use of different enzymes viz. pectinase, cellulase and pectinase CCM alone or in combinations to enhance olive oil recovery and quality. The enzymatic treatment significantly (P < 0.05) increased the oil yield and clarity of oil without adversely affecting the quality parameters. The combination of pectinase + cellulase (1:1) at 0.05% gave maximum oil recovery (11.0%), clarity (optical density = 0.242) and total phenols (165 mg/kg) compared with untreated samples. The oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In some previous studies, the increase in extraction yield was done using enzymatic treatment as reported by Sharma et al . () and Najaifan et al . ().…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In some previous studies, the increase in extraction yield was done using enzymatic treatment as reported by Sharma et al . () and Najaifan et al . ().…”
Section: Introductionmentioning
confidence: 90%
“…The insufficient yield is the main problem facing solventfree edible oil extraction. In some previous studies, the increase in extraction yield was done using enzymatic treatment as reported by Sharma et al (2015) and Najaifan et al (2009). The selection of a suitable enzyme is an important factor since every ingredient has a specific cell wall structure (Chen and Diosady, 2003).According to Ranalli et al (2003) to recover oil which is enclosed in the cell by breaking the cell wall, pectolytic, cellulolytic and hemi cellulolytic species are applied.…”
Section: Introductionmentioning
confidence: 99%
“…During mixing, the use of cellulases alone or in combination with pectinases enhances the extraction yield as well as the oil quality. Moreover, such treatment modifies the organoleptic properties of olive oil since it promotes the release of several phenolic compounds [152]. In addition, cellulases in combination with other CWLEs, such as xylanase, find application in the bakery industry since their use improves the loaf volume and bread quality [153,154].…”
Section: Use Of Plant-expressed Cwles In Medical and Nutraceutical Fimentioning
confidence: 99%
“… Studies in pilot/industrial scale : Aguilera et al (, ); Caponio et al (); Caponio et al (); García et al (); Moya et al (); Ranalli and De Mattia (); Ranalli et al (, , b, , b, c, ); Sadkaoui et al (, ); Sharma et al (); Squeo et al (); Tamborrino et al ().…”
Section: Malaxationmentioning
confidence: 99%
“…In consequence, the oil produced using enzymatic treatment can be classified as “olive oil” given that the rest of quality criteria are fulfilled. Nevertheless, there is a lot of literature focusing on enzymes as processing aids for olive oil extraction in the last 20 years (Aliakbarian et al, ; De Faveri et al, ; Najafian et al, ; Ranalli et al, , , b, c, , ; Ranalli and De Mattia, ; Sharma et al, ; Vierhuis et al, ). The role of enzymes in olive oil processing is to degrade the cell walls (where oil is contained) as well as pectins, which act as stabilizers in emulsions (Ranalli et al, ).…”
Section: Malaxationmentioning
confidence: 99%